A Molecular Popeye: Li+@C60 and its Complexes with [n]Cycloparaphenylenes - Freiberger, Markus; Solymosi, Iris; Freiberger, Eva Marie; Hirsch, Andreas; Perez-Ojeda Rodriguez, Maria Eugenia; Drewello, Thomas (Nanoscale, 2023)
In this work, we compare for the first time the stability of [n]cycloparaphenylene ([n]CPP)-based host–guest complexes with Li+@C60 and C60 in the gas and the solution phase. Our gas-phase experiments reveal a significant increase in stability for the complexes featuring [9–12]CPP with Li+@C60. This increased interaction strength is also observed in solution. Isothermal titration calorimetry shows for the formation of [10]CPP⊃Li+@C60 a two orders of magnitude larger association constant than that for the C60 analog. Additionally, an increased binding entropy is observed. This study contributes to a better understanding of host–guest complexes between [n]CPPs and endohedral metallofullerenes at a molecular level, which is the prerequisite for future applications.